Sustainable mined lands rehabilitation using landscape biomimicry - Smetana, S.M.; Smetana, O.M. (Екологія і природокористування, 2013)
Article reviews main theoretical and practical issues in the field of biomimicry at landscape level for mined lands rehabilitation. It also includes a successful practical case study of biodiversity development centers creation on open-cut mining lands.